Theoretical approach for the praxis of advanced management of the university system - Marcial, Diego; Covis, Roselin (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
This research was aimed at reviewing the praxis of advanced management of university leaders, where the praxeology and ways of performing management were reviewed. A theoretical approach was made on the praxis of advanced management in education from an ontological phronesis for the formation of leaders in the university system of Chile. Theoretical elements such as Praxeology, Advanced Educational Management, Leadership and University System were developed with epistemological implications through Habermas' theories of communicative action, epistemological obstacles according to Bachelard and Weber's bureaucratic theory.